Examining Mindfulness to Develop Student Psychological Well-Being: The Role of Resilience and Self-Compassion - Martono, S; Prajanti, Sucihatiningsih Dian Wisika; Khoiruddin, M.; Purwanta, Edi; Dwiningrum , Irene Astuti (Migration Letters, 2023)
This study aims to explore the effects of student mindfulness on psychological well-being through student resilience and self-compassion. Nowadays, student psychological well-being is prominent in encouraging student success in academics. The research employs a quantitative approach to examine the data, using a sample of 173 students from public universities in Indonesia. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) is used to analyze the data. The research findings demonstrate that mindfulness positively correlates with psychological well-being, and this relationship is mediated by both student resilience and self-compassion. By developing adaptive coping strategies and approaching challenges with equanimity, mindfulness enhances student resilience. Moreover, mindfulness interventions cultivate self-compassion, leading to reduced self-criticism and increased emotional well-being. The interactive effect of resilience and self-compassion reinforces the positive outcomes of mindfulness on psychological well-being. This study emphasizes the importance of adopting a holistic approach to student well-being, promoting mindfulness in educational settings, and proactively addressing the mental health needs of students. As educational institutions prioritize student mental well-being, mindfulness emerges as a powerful tool in nurturing resilient, compassionate, and psychologically healthy individuals.